Screening and Characterization of Biofilm Formation by Staphylococcus Spp and Pseudomonas Spp Isolates from Diabetic Foot Ulcer: Life Sciences-Microbiology for health care - Ramasamy Venkatesan; Suresh S S Raja; Vijayakumar.R; Panneer Selvam.K (International Journal of Life Science and Pharma Research, 2022)
Diabetes mellitus is a very serious systemic disease worldwide. Around 416 million cases were estimated in 2015 worldwide, and are expected to reach 549 million in 2030 which is 8.6% higher. Diabetes mellitus is the leading cause of mortality and morbidity and is responsible for 3.8 million deaths annually. 25% of the diabetic patients are affected with foot infections out of which, 15% people are forced for limb amputation which affects the quality of life of the patients. Diabetic foot ulcer is a poly microbial infection mostly occurs due to Staphylococcus spp and Pseudomonas spp and pose serious complications. Bacteria are the cause for much type of diseases and generate resistance to wide range of biofilm forming. Biofilms constitute reservoirs of pathogens and are associated with resistance to antimicrobial agents and chronic infection. The study included 156 patients (59% male and 41% female) suffering diabetic foot ulcer whose pus culture was isolated. The identification of isolates for both gram-negative and gram-positive organisms was done as per the procedures mentioned in Bergey’s manual of Determinative Bacteriology. Further, MALDI- TOF (Matrix-Assisted Laser Desorption/Ionization) was used to confirm the identification of the isolates using classical methods. Staphylococcus spp (65%) and Pseudomonas spp (35%) biofilm producing isolates were identified for Congo red method assay and Tissue culture plate method. Results of biofilm production in positive, intermediate, negative differentiation on the Congo red plate assay and Tissue culture plate method assays were analyzed.